Synthesis, characterization and crystal structure of a novel tetranuclear Co(II) cubane cluster - Chen, Hong; Wu, Jianchun; Liu, Mingguo (European Journal of Chemistry, 2019)
A new tetranuclear Co(II) cubane cluster 1, [Co4(L1)4(L2)4]·4CH3CH2OH (HL1 = 2-Methylquinolin-8-ol, HL2 = t-Bu-COOH), has been synthesized and characterized by X-ray single crystal diffraction, FT-IR, TG/DSC, and elementary analysis. The data reveals that it has a very interesting structural motif consisting of a [Co4O4] core in the form of a cube with the Co and O occupying opposite corners. In the crystal structure of complex 1, the molecules are linked by intramolecular C−H···O hydrogen bonding interactions and Van der Waals forces, forming a three-dimensional network structure. Crystal data for complex 1: C60H68Co4N4O12, triclinic, space group P-1 (no. 2), with a = 12.0644(4), b = 12.0996(3), c = 20.2858(7) Å, α = 92.005(3)o, β = 92.182(3)°, γ = 97.943(3)°, Z = 2, V = 2928.25(16) Å3, T = 293 K, μ(MoKα) = 1.178 mm-1, Dcalc = 1.444 g/cm3, 16737 reflections measured (3.00° ≤ θ ≤ 28.53°), 9010 unique (Rint = 0.024, Rsigma = 0.0574) which were used in all calculations. The final R1 was 0.039 (I≥2σ(I)) and wR2 was 0.090 (all data).